Computer Network Design Using the Simple Queue Method in Maximising Network Performance in Companies - Basar, Abdul Rohmad; Jalil, Siti 'Afiat; Adi, Novi Hendri; Gunawan, Raja Hayri (Journal of Computer-based Instructional Media, 2023)
Computer Network Design Using the Simple Queue Method at CV. Ide Maju Berkarya is made to maximise the performance of existing networks in the company. This design is to provide network capacity for users evenly using the Simple Queue method and can monitor the existing network in the company so that there can be no more problems in getting network capacity where previously the capacity that each user got was uneven. This computer network design is based on a case study at CV. Ide Maju Berkarya which lasted for 4 (four) months. The object of activity carried out in the form of direct observation to the field to see the circumstances and situations that occur, how the performance of the existing network at CV. Ide Maju Berkarya. From the conditions that occur in the field, it can be seen that the distribution of nets for each employee is not evenly distributed, there is no network that can monitor the network in the company so that problems often occur when using the internet becomes slow and disconnected. Conclusions and suggestions on the design of this computer network are to be able to improve the performance of existing networks in the company by sharing the capacity of each user evenly when using internet access in the company and can monitor traffic and users connected to the network.